L'arte rupestre nella penisola e nelle isole Italiane : rapporti tra rocce incise e dipinte, simboli, aree montane e viabilità = Rock art in the Italian Peninsula and islands : issues about the relation between engraved and painted rocks, symbols, mountain areas and paths - Carrera, Francesco M. P.,; Grifoni Cremonesi, Renata,; Tosatti, Anna Maria, (Access archaeology., 2021)
This book presents the proceedings of IFRAO 2018 - Session 2H. The various papers present a remarkable synthesis of current knowledge on inscriptions, engraved and painted, on the rock walls of the Italian peninsular.